Sosialisasi Oral Hygiene Sebagai Upaya Meningkatkan Pengetahuan Dan Perilaku Hidup Bersih Pada Anak - Yuliani, Feri Catur; Vitriana Permatasari; Yosi Murtiwi; Tio Kresiyanto; Sri Wahyu Utami (LP3M Universitas Putra Bangsa, 2025)
Oral hygiene in an effort to maintain oral health is very important, problems in oral health occur due to lack of awareness in performing oral hygiene. The mouth and teeth are one of the entrances of microorganisms such as fungi, bacteria and so on which can cause health problems. This community service activity aims to increase early childhood knowledge about the practice of maintaining oral health. The method of activity that the author uses is counseling and mentoring with lecture, discussion, and demonstration methods on how to brush teeth properly and correctly. This activity was attended by 25 participants. The results of the questionnaire showed that most of the participants had not implemented good oral hygiene behavior. Participants followed this counseling with enthusiasm and the evaluation results showed that all participants understood the behavior of maintaining oral hygiene, namely knowing how to brush their teeth and how to maintain cleanliness in brushing their teeth.